Estudo paramétrico do comportamento geotécnico de estruturas de contenção de solo reforçado - Sarmento Junior, Rogério Gonçalves (2018)
The use of reinforced soil wall (RSW) is a geotechnical response to the quick human dense settlement in urban areas. Techniques that insert elements in the soil mass in order to improve its resistance are very ancient in engineering history. In 1966, French architect Henry Vidal developed the first RSW design method, known as Terre Armée (Reinforced Soil). Currently, the development of new materials and construction techniques have enabled RSW to become more complex and sophisticated. Analysing the influence of the soil compaction and of the facing structure allows a deeper understanding of geotechnical behaviour of RSW. In order to evaluate the impact of soil compaction and facing system in RSW, this work performs computational analyses in different RSW using the finite element method. The finite element method was adopted because it provides more accurate and direct representation to complex real problems such as earthwork structure behaviour. The CRISP92-SC, software created on Cambridge University, performed a computational simulation of RSW. The Modified K-Stiffness (2008) and Dantas and Ehrlich (2000) calculation method were used and their results compared to those obtained in numerical simulations. Initially, the influence of the element of discretization was checked using the finite element mesh. The goal was to investigate if the use of different mesh elements could lead to distinct results to the same problem. In a second time, the impact of the compaction and of the type of facing used was verified. For that, results from Almeida (2014) together with the data obtained from this research for structures submitted to the compaction process were employed. The results showed that the compacting had a great influence on the final behaviour of the RSW. Its influence does not correspond only to the effect usually attributed to compaction in common earthwork calculations. Other effects were detected. Ignoring this fact can underestimate the stress on the reinforcement at the lower depths of RSW. The RSW facing structure may also exert a great influence on deformation and on resistance. Some types of facing could have a relevant impact on restricting the displacement of RSW base and their effect should not be neglected.